Sandy Jacobs-Tolle COVID-19 Knit Glove Social Media Post - Jacobs-Tolle, Sandy::::::::: (2022)
One in a series of six social media posts showing Sandy Jacobs-Tolle's COVID-19 knitting projects. The contributor writes that these were ". . . made during quarantine, late March to early April. Knitting has frequently been a source of comfort and thoughtful action in times of stress and isolation."